2017
DOI: 10.1002/dta.2161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of six ‘neuro‐enhancing’ phenidate analogs

Abstract: Six collected phenidates, i.e. 4-methylmethylphenidate, 3,4-dichloromethylphenidate, ethylphenidate, 3,4-dichloroethylphenidate, ethylnaphthidate and N-benzyl-ethylphenidate were fully characterized by means of X-ray, NMR, GC-MS, ESI-MS Running title: Analytical characterization of six phenidate analogs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Interestingly, the formation of the GC-induced product, methyl 4-fluorophenyl acetate, was found to be slightly higher (53.6 %) in the chromatogram of the (±)- threo - 4FMPH racemate, compared to that of the (±)- erythro - 4FMPH racemate (43.7%). This type of degradation was consistent with literature reports on methylphenidate and its analogs [29,4748] , however, the suggested identity remains tentative as a reference standard was not available.…”
Section: Analytical Featuressupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the formation of the GC-induced product, methyl 4-fluorophenyl acetate, was found to be slightly higher (53.6 %) in the chromatogram of the (±)- threo - 4FMPH racemate, compared to that of the (±)- erythro - 4FMPH racemate (43.7%). This type of degradation was consistent with literature reports on methylphenidate and its analogs [29,4748] , however, the suggested identity remains tentative as a reference standard was not available.…”
Section: Analytical Featuressupporting
confidence: 90%
“…[28] Comprehensive analytical characterizations have recently been described for 4-methylmethylphenidate, 3,4-CTMP, ethylphenidate, 3,4dichloroethylphenidate, N-benzyl-ethylphenidate and ethylnaphthidate (HDEP-28), respectively. [29] Recent studies from the UK associated ethylphenidate use with adverse reactions including deaths. [30][31][32] In addition, it was reported that injection was a common route of administration, thus adding the risk of harms associated with this method of administration.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, WADA's Prohibited List sustained the existence of 2 groups of stimulants namely non‐specified and specified compounds. Of note, despite the ever‐growing plethora of “designer” psychoactive substances (including psychostimulants), which have urged forensics and toxicology laboratories to continuously refine testing capabilities, the frequency at which such designer compounds are determined in doping controls is still comparably low.…”
Section: Stimulants Narcotics Cannabinoids and Glucocorticoidsmentioning
confidence: 99%
“…Several scientific articles have been published in recent years regarding analytical characterization of phenidate analogues by nuclear magnetic resonance (NMR), infrared (IR) spectroscopy, gas chromatography‐mass spectrometry (GC‐MS), and liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC‐ESI‐MS/MS) . The confirmation of such chemical identities by MS techniques represents a challenging task because these analogues present information‐poor mass spectra in LC‐ESI‐MS/MS and in GC‐EI‐MS analysis, with a fragment/product ion representing mainly or only the secondary amine‐containing residue.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of information is attributed to the strong tendency of the amine residue (piperidine) to stabilize the positive charge and leads to unavoidable ambiguity in the identification process. Furthermore, phenidate analogues are difficult to identify by GC‐MS, because they undergo thermal decomposition (pyrolysis) in the injection port and/or on column under standard GC‐conditions . The availability of high‐resolution accurate mass spectrometry (HRMS), which generally provides essential tools for the identification of unknowns of interest including novel drugs and their metabolites, is also not sufficient to determine the exclusive chemical structure of the molecule .…”
Section: Introductionmentioning
confidence: 99%